PENGARUH KINERJA DAN DISIPLIN APARATUR SIPIL NEGARA (ASN) TERHADAP KUALITAS PELAYANAN PADA BAGIAN PEMERINTAHAN DESA SEKRETARIAT DAERAH KABUPATEN PESAWARAN - M Fikri Akbar; Dina Sasri Megawati (e-JKPP, 2019)
The problems in this study are: (1) Does the Performance of the State Civil Apparatus  affect the Quality of Service in the Village Administration Section of the District of Pesawaran District (2) Does the Discipline of the Civil Service  affect the Quality of Service at the Government Division of the Regional Secretariat Village Pesawaran Regency(3) Does the Performance and Discipline of the State Civil Apparatus  jointly influence the quality of service in the Village Administration Section of the Pesawaran Regency Regional Secretariat.This research uses analytical survey method. This study aims to analyze the influence between the variables studied, namely state civil apparatus Performance (X1),  Discipline (X2), improve service quality (Y) in this study used quantitative research types to verify the research hypothesis. These methods and techniques were chosen because they allow a more extensive study of the influence of the research variables.The results showed that there was a significant influence of both state civil apparatus performance and state civil apparatus discipline on service quality in the Village Administration Section of Pesawaran District Regional Secretariat, the greatest influence of state civil apparatus performance variables and state civil apparatus discipline was state civil apparatus Performance variable which was 69.03 percent or was in the high category , state civil apparatus discipline is 67.96 percent, or it is in the sufficient category. Based on the results of the study, that the contribution of  state civil apparatus Performance variables and state civil apparatus discipline to service quality, is in the quite good category but not yet optimal. This is due to the relative lack of work facilities and the absence of optimal application of regulations, so that employees have not been able to carry out their duties optimally, which results in suboptimal quality of service in the Village Administration Section of the District of Pesawaran District